Alcohol intake, alcoholic beverage type and multiple myeloma risk: a meta-analysis of 26 observational studies. Issue 5 (May 2015) - Psaltopoulou, Theodora; Sergentanis, Theodoros N.; Sergentanis, Ioannis N.; Karadimitris, Anastasios; Terpos, Evangelos; Dimopoulos, Meletios A.
Abstract: This meta-analysis aimed to examine the association between alcohol consumption and multiple myeloma (MM) risk. Eligible publications were sought in PubMed to 31 December 2013. Separate analyses were performed by study design, gender, alcoholic beverages and levels of consumption. Sixteen case–control studies (3921 cases and 19 594 controls) and 10 cohort studies (3167 incident cases in total cohort of 2 557 649 subjects) were eligible. Ever consumption of alcohol was associated with reduced MM risk (pooled relative risk [RR] = 0.88, 95% confidence interval [CI]: 0.79–0.99) and especially consumption of wine correlated with reduced MM risk (pooled RR = 0.77, 95% CI: 0.67–0.89 for ever drinkers). MM risk was not affected by beer or liquor intake. A protective association was observed among females (pooled RR = 0.79, 95% CI: 0.69–0.89 for ever drinkers), whereas the association among males seemed null. In conclusion, contrary to most solid tumors, alcohol intake may confer protection in terms of MM risk among females, with wine being particularly beneficial.